CWT x DWT x DTWT x SDTWT: Clarifying terminologies and roles of different types of wavelet transforms - Guido, Rodrigo Capobianco [UNESP] (2020)
Wavelets have been placed at the forefront of scientific researches involving signal processing, applied mathematics, pattern recognition and related fields. Nevertheless, as we have observed, students and young researchers still make mistakes when referring to one of the most relevant tools for time-frequency signal analysis. Thus, this correspondence clarifies the terminologies and specific roles of four types of wavelet transforms: The continuous wavelet transform (CWT), the discrete wavelet transform (DWT), the discrete-time wavelet transform (DTWT) and the stationary discrete-time wavelet transform (SDTWT). We believe that, after reading this correspondence, readers will be able to correctly refer to, and identify, the most appropriate type of wavelet transform for a certain application, selecting relevant and accurate material for subsequent investigation.